2009
DOI: 10.1016/s1472-6483(10)60030-2
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant hyaluronidase (Cumulase®) improves intracytoplasmic sperm injection survival and fertilization rates

Abstract: The cumulus-corona-oocyte complex, composed of cumulus granulosa cells embedded in a matrix of hyaluronan oligosaccharide chains cross-linked by hyaluronan binding proteins and proteoglycans, surrounds each oocyte and must be removed prior to intracytoplasmic sperm injection (ICSI). This is traditionally achieved using enzymatic digestion of the matrix with a bovine-derived hyaluronidase followed by mechanical denudation through pipetting. A human recombinant hyaluronidase (Cumulase) has been developed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Animal-derived products have limited purity and accidental transmission of pathogens cannot be excluded fully. These limitations inevitably imply an increased need for mechanical dispersal of the cumulus and corona by means of multiple pipetting, which could be harmful to the oocyte [27]. Evison and De Vos reported that the use of human recombinant hyaluronidase could improve ICSI survival and good embryo development compared with bovine hyaluronidase [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Animal-derived products have limited purity and accidental transmission of pathogens cannot be excluded fully. These limitations inevitably imply an increased need for mechanical dispersal of the cumulus and corona by means of multiple pipetting, which could be harmful to the oocyte [27]. Evison and De Vos reported that the use of human recombinant hyaluronidase could improve ICSI survival and good embryo development compared with bovine hyaluronidase [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the enzyme detaches cumulus cells from the ovum in the process of denudation, where enzymes break down the ECM consisting of HA; rHuPH20 is increasingly used here as well. Studies show higher fertilisation rates as well as a reduction of oocyte damage when rHuPH20 is used compared to bovine HAase [91]. Recent articles deal with the use of HAase to enhance drug delivery in subcutaneously applied therapeutic agents.…”
Section: Potential Of Clinical Use Of Haasementioning
confidence: 99%
“…Oocytes are traditionally denuded using bovine testis-derived hyaluronidase that affects the quality of oocytes and embryos [5]. In hospitals, human recombinant hyaluronidase was commercially used as an alternative to bovine-derived hyaluronidase owing to its purity, safety, and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Ishizuka et al have shown that prolonged treatment with hyaluronidase decreases the quality of mouse oocytes and that a shorter exposure time increases fertilization and developmental ability [9]. Furthermore, human oocytes treated with hyaluronidase have also been shown to have decreased oocyte survival, fertilization rates, and developmental ability following ICSI [4,5,10]. In pigs, the effect of different denuding procedures on oocyte damage and embryo development has previously been investigated [11].…”
Section: Introductionmentioning
confidence: 99%